Os Últimos Vinte Anos do Prémio Valmor e Municipal de Arquitectura - Rita Mota de Miranda (2010)
This Master's term paper aims to focus on Valmor Award's last twenty years (it was founded in 1902), period in which this merged with the Municipal Architecture Award and in which its regulation was redrawned - from 1982 to 2002. The award intended to recognize, every year, the "most beautiful building, or built house in Lisbon"*. A hundred and eight years after its institution, this award, besides it's seniority and unrivalled popularity between the common citizen (besides architects), even if only in the city of Lisbon, has resisted to the passage of time and several apparent abandons, contributing towards a general architecture panorama, in that city and a bit all over the country, throughout these years. Regarding this, and to contextualize eras and architectures, a brief analysis of the first eighty years is made, emphasizing the social-political climate of each moment, as well as its respective decisions and important marks. Justified by instability climates, uncertainty and/or oppression, some significant pieces that were put apart from the awarded list are also mentioned. Actually, this is another of the curious characteristics of the award: even if not all the nominations correspond, faithfully, to the best architecture developed in the city and even less in the country, they can't help show, for the good and not so good examples, what were the tendencies and predominant tastes corresponding to each era, allowing a critical analysis of the city's architecture throughout them. After this historical appreciation and revision of all the changes that occurred on the award's regulation, we entered in the main focus of this dissertation, wishing with it, not only to portrait what was Lisbon architecturally over the last years, through the approach and systematic analysis of the awarded pieces with the Valmor and Municipal Architecture Award, but also contextualizing political and socially. For that, I resorted to authors like José Manuel Pedreirinho, José Manuel Fernandes or Marina Tavares Dias, between others, for a global analysis; to sporadic publications of critics regarding each piece or the award itself, as well of the own architects authorship; and also to the research and collection of information at Lisbon Municipal Archives ("Arco do Cego" and "Intermédio"), as of minutes, regulation and construction site volumes. As a requiem, this test wishes to catch the attention not only for the negligence and lack of attention that architecture still suffers from in Portugal, but also for the lack of critic and political influences that fail to contribute to the communication of a clear and significant message, especially to classes unfamiliar to it.